The Role of the Social Worker in Supporting University Students Psychologically and Socially: A Study of Jordanian University Students - Al-Raggad, Fatima Eed; Alsabeelah, Amal Metleb (Journal of Posthumanism, 2025)
This paper examines the role of social workers in addressing the psychological and social needs of university students, with a focus on undergraduate students at Princess Alia University College, a branch of Al-Balqa Applied University in Jordan. Data were analyzed using a qualitative research design, in which semi-structured interviews were conducted to collect data from ten undergraduate students representing various academic years and disciplines. The results outline three main patterns: the importance of awareness and accessibility of social work services, the role of trust and confidentiality in developing students’ willingness to seek help, and the influence of contact with social workers on the psychological wellbeing and sense of belonging of students. Findings indicate that although students appreciate the roles of social workers, awareness and logistical problems (including delays and availability of services) tend to limit access. Confidentiality was also a vital factor in the disclosure of personal problems by students, resonating with past literature that highlights the moral aspect of social work. Furthermore, it was found that positive experiences with social workers resulted in a decrease in stress, an increase in coping strategies, and a sense of belonging within the university setting. The research would be a valuable addition to the literature, as it offers a cultural contextualization of research in Jordan, which can be used to emphasize the importance of universities enhancing their awareness programs, simplifying service delivery, and increasing social work facilities to address the psychological and social needs of students. Policy and practice recommendations are provided to ensure the improved visibility and performance of social work services in higher education.